Dentomaxillofacial radiology in Australia and dentist satisfaction with radiology reports. (26th July 2018) - Selim, DG; Sexton, C; Monsour, P
Abstract: Background: Dentomaxillofacial Radiology (DMFR) is comprised of the smallest cohort of specialists in Australia. A survey was undertaken to assess awareness of DMFR, radiology reporting and referring protocols as well as dental practitioners' satisfaction with their radiology reporting arrangements. Methods: An original online survey created using Checkbox † was sent to dental practitioners. The survey was promoted on Australian‐based dental Facebook forums and emailed to targeted members via Australian professional dental associations. Results: A total of 399 responses were received, with over 80% of respondents aware of DMFR as a specialty. Approximately 40% of practitioners were self‐reporting their imaging. There was correlation between increased satisfaction with external reporting and utilization of DMFR services and decreased satisfaction with medical radiology services. More than 90% of general dentists and greater than 85% of dental specialists prefer DMFR reports to medical radiology reports. Approximately 80% of practitioners believed that their satisfaction would change positively if they had access to a DMFR report. Conclusion: The research indicates a high degree of self‐reporting or non‐reporting by dental practitioners. There is low satisfaction with external reporting performed by Medical Radiologists primarily due to a lack of dental knowledge or detail and a preference for DMF Radiology reports.